On the way to understand responsible business - CSV and ESG concepts from employees` perspective - Lemańczyk, Joanna; Kubala, Maria (Zielona Góra: Faculty of Economics and Management Press)
The main aim of this article is to explore how employees are aware of and perceive companies` commitment to environmental and social issues through the concepts of Creating Shared Value (CSV) and Environmental, Social, and Governance (ESG). The authors begin with a critical review of the theoretical background of Corporate Social Responsibility (CSR). Then, they highlight and compare a shift towards the more profit-oriented CSV and ESG concepts.
Keywords: CSR; ESG; CSV; employee awareness